Different Eating Habits Are Observed in Overweight and Obese Children Than in Normal-Weight Peers - Żaneta Malczyk; Agnieszka Pasztak-Opiłka; Agnieszka Zachurzok (MDPI AG, 2024)
Background: Obesity is diagnosed in 13.6% of early primary school children in Poland. Its presence at this age increases the risk of obesity occurrence in adulthood. Therefore, it is important to properly shape eating behaviors at the stage of childhood and identify incorrect eating styles. Methods: This study aimed to investigate whether overweight and obese children differ significantly from children with normal body weights in terms of their eating styles. For the materials and methods, 43 mothers of overweight or obese children aged 3-10 years and 88 mothers of normal-weight children aged 3-10 years completed a questionnaire related to sociodemographic factors and the Children's Eating Behaviour Questionnaire. Results: The overweight and obese children, compared with normal-weight children, scored higher on the food responsiveness (p = 0.009) and emotional overeating (p = 0.013) scales and lower on the satiety responsiveness (p = 0.025) and slowness in eating scales (p < 0.0001). No significant difference was found for other subscales between the studied groups. In the group of overweight and obese children, the child's age correlated negatively with enjoyment of food, as did the mother's BMI with slowness in eating. Conclusions: The results indicate the presence of significant differences in eating styles between normal-weight children and overweight or obese children. Identifying families at high risk of inappropriate eating behaviors and educating them appropriately can reduce the risk of children becoming overweight or obese.